Meningkatkan Pengetahuan Kebencanaan Siswa Sekolah Dasar Melalui Snake Board Edu-Game - Syamsul Bachri; Tabita May Hidiyah; A.Riyan Rahman Hakiki; Nanda Regita Cahyaning Putri; Mellinia Regina Heni Prastiwi (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2024)
Disaster education is essential to implement from an early age. However, there are still limitations in its implementation, such as the lack of models and media that support disaster education. This community service program aims to enhance the disaster knowledge and awareness of students at Jambewangi 3 Elementary School through the use of interactive learning media, specifically the Snake Board Edu-Game. The program involves the development and application of an educational game designed to teach students about various types of natural disasters, such as earthquakes, floods, and volcanic eruptions, as well as mitigation steps and responses. During the activities, students are encouraged to actively participate in game sessions that combine educational and interactive elements, promoting enjoyable and effective learning. The results of the program show an increase in students' knowledge about disasters. Additionally, students demonstrated high enthusiasm and improved ability to identify appropriate steps to deal with emergency situations. The program was also well-received by teachers and students, who see the potential of the Snake Board Edu-Game as an innovative learning tool that can be integrated into the school curriculum, particularly in disaster education.